Pharmacological Targeting of Plasminogen Activator Inhibitor-1 Decreases Vascular Smooth Muscle Cell Migration and Neointima Formation. Issue 11 (November 2016) - Ji, Yan; Weng, Zhen; Fish, Philip; Goyal, Neha; Luo, Mao; Myears, Samantha P.; Strawn, Tammy L.; Chandrasekar, Bysani; Wu, Jianbo; Fay, William P.
Abstract : Objective—: Plasminogen activator inhibitor-1 (PAI-1), a serine protease inhibitor that promotes and inhibits cell migration, plays a complex and important role in adverse vascular remodeling. Little is known about the effects of pharmacological PAI-1 inhibitors, an emerging drug class, on migration of vascular smooth muscle cells (SMCs) and endothelial cells (ECs), crucial mediators of vascular remodeling. We investigated the effects of PAI-039 (tiplaxtinin), a specific PAI-1 inhibitor, on SMC and EC migration in vitro and vascular remodeling in vivo. Approach and Results—: PAI-039 inhibited SMC migration through collagen gels, including those supplemented with vitronectin and other extracellular matrix proteins, but did not inhibit migration of PAI-1-deficient SMCs, suggesting that its antimigratory effects were PAI-1-specific and physiologically relevant. However, PAI-039 did not inhibit EC migration. PAI-039 inhibited phosphorylation and nuclear translocation of signal transducers and activators of transcription-1 in SMCs, but had no discernable effect on signal transducer and activator of transcription-1 signaling in ECs. Expression of low-density lipoprotein receptor–related protein 1, a motogenic PAI-1 receptor that activates Janus kinase/signal transducers and activators of transcription-1 signaling, was markedly lower in ECs than in SMCs. Notably, PAI-039 significantly inhibited intimal hyperplasia and inflammation in murine models of adverse vascular remodeling, but did not adversely affect re-endothelialization after endothelium-denuding mechanical vascular injury. Conclusions—: PAI-039 inhibits SMC migration and intimal hyperplasia, while having no inhibitory effect on ECs, which seems to be because of differences in PAI-1-dependent low-density lipoprotein receptor–related protein 1/Janus kinase/signal transducer and activator of transcription-1 signaling between SMCs and ECs. These findings suggest that PAI-1 may be an important therapeutic target in obstructive vascular diseases characterized by neointimal hyperplasia. Abstract : Supplemental Digital Content is available in the text.